Digestible energy of unpeeled cassava root meal and its effect on growth performance and carcass traits in rabbits - L.M. Mora; A.S.A.M.T. Moura; C. Scapinello; S.J. Bicudo; I.G. Araújo; F. Curcelli; T.F.M. Barros (World Rabbit Science, 2014)
Two experiments were conducted to evaluate the use of cassava root meal (891 g dry matter [DM]/kg, 639 g starch/kg, 74.1 g neutral detergent fibre [NDF]/kg, and 26.6 g crude protein [CP]/kg) in diets for growing rabbits. In the first experiment, a basal diet (419 g NDF/kg and 181 g CP/kg) and a test diet, in which cassava replaced 25% of the DM of the reference diet, were used. Twenty 50-d-old New Zealand White rabbits weighing 1474±10 g were randomly assigned to the 2 treatments, and digestibility of DM and gross energy (GE) were determined. The inclusion of cassava root meal in the diet increased DM digestibility (67.0±0.80 vs. 58.0±1.12%, P<0.01) and digestible energy (DE) content (11.86±0.16 vs. 10.45±0.22 MJ/kg, P<0.01). Digestible DM and DE contents of the unpeeled cassava root meal, obtained by the substitution method, were 943.3±15.8 g/kg and 15.28±0.32 MJ/kg. In the second experiment, 5 experimental diets were formulated to contain 150 g CP/kg, 184 g acid detergent fibre/kg and 10.9 MJ DE/kg, and increasing levels (0, 7, 14, 21 and 28%) of unpeeled cassava root meal, mainly in substitution of corn. A growth trial was carried out using 90 rabbits from the Botucatu genetic group from weaning (35 d, weighing 951±13 g) up to 71 d of age. The rabbits were housed in pairs, and randomly assigned to the 5 treatments (9 replicates/ treatment). No effect of the substitution of corn with cassava root meal was detected on growth performance (growth rate, feed intake and feed conversion ratio, on av. 44.6±0.50 g/d, 132±1.4 g/d and 2.97±0.028 g/g, respectively). The level of inclusion of cassava root meal had a quadratic effect (P=0.005) on the dressing out percentage, showing a minimal value (51.2%) for inclusion of 139 g/kg. No other effect was observed on slaughter and reference carcass weights (2383±19 and 1238±11 g, respectively). Unpeeled cassava root meal may be used to completely replace corn in the diet, supporting high performance in growing rabbits, but its effects on carcass traits should be investigated further.